PERBEDAAN TINGKAT KECEMASAN ANTARA SISWA YANG TERPAPAR PORNOGRAFI DENGAN SISWA YANG TIDAK TERPAPAR PORNOGRAFI DI SMA X KOTA MEDAN - RIZANA, RARA; NURALITA, NANDA SARI; NURHASANAH, NURHASANAH (LP2MTBM MAKARIOZ, 2023)
Anxiety is a feeling of unclear, unpleasant feeling, excessive worry, fear, surprise and helplessness that can interfere daily life. One of the things that can cause anxiety is exposure to pornography. With the development of technology, pornography is not only consumed by adults but can be freely accessed by children and adolescents. Indonesia itself is ranked third with the most access to pornography in the world. In research on adolescents aged 18 years and over, it was found that the prevalence of anxiety, depression and stress caused by addiction to watching pornography reached up to 13.5%. In addition, exposure to pornography in children and adolescents, whether intentional or unintentional, will greatly affect the brain, mentality and behavior. This type of research is an observational analytic study with a cross-sectional study design of students at SMA X Medan City. The sample is 207 people collected using the Simple Random Sampling technique Probability Sampling method. This study uses primary data by providing a questionnaire using the Google form. The result of this research obtained by most respondents aged 17 years (60.5%), sex dominated by women (67.1%). The highest level of anxiety for those who exposed to pornography is mild anxiety (24.3%), likewise with students who were not exposed to pornography, the level of mild anxiety also obtained the highest number (32.4%). The results of the analysis of differences in anxiety levels between those who exposed to pornography and those who not exposed to pornography were P = 0.000 (P <0.05). In this study there were differences in the level of anxiety between students who were exposed to pornography and students who were not exposed to pornographic content at SMA X Kota Medan.